Ijmuiden Holandia - Górska, Krystyna (1921-2012). ([Sopot], 1956)
Przedstawia widok na nabrzeże morskie.
U dołu pod kompozycją ołówkiem tytuł, sygnatura autora i data.
Keywords: Grafika -- Polska -- 1945-1970.